Electronics for Guitarists - Dailey, Denton J.; SpringerLink (Online service) (New York, NY : Springer New York, 2011)
Electronics for Guitarists teaches the basic theory of operation and design principles of analog guitar signal processing circuits and amplifiers. The design and operation of common effects circuits such as tone controls, preamps, phasers, flangers, envelope followers, distortion and overdrives are covered, as are both solid-state amplifiers and power supplies. Written specifically for the guitarist, this book balances coverage of theoretical analysis and design while providing many examples of practical experimental circuits. The main thrust of the material is old school analog circuitry, focusing on: Fundamental principles of transistors Integrated circuit and vacuum tube-based amplifier operation Theory and operation of typical guitar signal processing effects circuits Electronics for Guitarists should be of interest to any musician that is interested in analog signal processing. The material covered is also useful to general electronics hobbyists, technologists and engineers that are interested in guitar and music-related electronics applications.
1: Power Supplies -- 2: Pickups, Volume and Tone Controls -- 3: Small-Signal and Low Power Amplifiers -- 4: Solid State Power Amplifiers -- 5: Guitar Effects Circuits -- 6: Vacuum Tube Amplifiers -- Appendix A: Selected Tube Characteristics Curves -- Appendix B: Useful Formulas and Equations -- Appendix C: Vacuum Tube Operating Principles.
Keywords: Engineering; Mathematics; Systems engineering; Engineering; Signal, Image and Speech Processing; Popular Science in Mathematics/Computer Science/Natural Science/Technology.; Circuits and Systems